A study on the valuation of football players as collateral. - Lim, Zhijuan. (2012)
In light of widening competitive disparity in the football industry and the recent collateralizations of Ronaldo and Kaka, this paper aims to investigate the conditions that would facilitate the use of football players as collateral. Correlation and multiple linear regression models were employed to derive the significant determinants of player valuation. It is found that a player’s position, number of goals scored last season, remaining contract length and buying clubs’ revenue and UEFA ranking are significant determinants of player value. In addition, a case study was conducted to examine the exceptional characteristics of Ronaldo, Kaka and Real Madrid that made collateralizing football players possible. It is surmised that Ronaldo’s and Kaka’s ability to exploit superstar economics as well as the qualitative aspects of Real Madrid’s financial position were also deciding factors in enhancing the collateralization’s feasibility.